Alternative pathways to sustainable development: Lessons from Latin America - Gilles Carbonnier; Humberto Campodónico Sánchez; Sergio Tezanos Vázquez (Brill Nijhoff, 2017)
This issue of 'International Development Policy' looks at recent paradigmatic innovations and development trajectories in Latin America, with a particular focus on the Andean region. After a period of robust growth, poverty alleviation and inequality reduction associated with high commodity prices, this issue examines the diverse development narratives and experiences in countries such as Bolivia, Colombia, Ecuador and Peru. Highlighting propositions such as "buen vivir", this thematic issue questions whether competing ideologies and discourses have translated into different outcomes, be it with regard to environmental sustainability, social progress, primary commodity dependence, or the rights and cultural identity of indigenous peoples. This collection aims to enrich our understanding of recent development debates and processes in Latin America, and what the rest of the world can learn from them.
Keywords: 330; Wirtschaftspolitik; Nachhaltigkeit; Entwicklungspolitik; Entwicklungstheorie; Lateinamerika